MXene-Based Electrochemical Biosensors: Advancing Detection Strategies for Biosensing (2020–2024) - Joydip Sengupta; Chaudhery Mustansar Hussain (Biosensors)
MXenes, a class of two-dimensional materials, have emerged as promising candidates for developing advanced electrochemical biosensors due to their exceptional electrical conductivity, large surface area, and rich surface chemistry. These unique properties enable high sensitivity, rapid response, and versatile functionalization, making MXene-based biosensors highly suitable for detecting biomolecules and pathogens in biomedical applications. This review explores recent advancements in MXene-based electrochemical biosensors from 2020 to 2024, focusing on their design principles, fabrication strategies, and integration with microfluidic platforms for enhanced performance. The potential of MXene sensors to achieve real-time and multiplexed detection is highlighted, alongside the associated challenges. Emphasis is placed on the role of MXenes in addressing critical needs in disease diagnostics, personalized medicine, and point-of-care testing, providing insights into future trends and transformative possibilities in the field of biomedical sensing technologies.